How does rapport impact knowledge transfer from older to younger employees? The moderating role of supportive climate - Rui, Hainan; Ju, Hailong (Frontiers in Psychology, 2022)
Knowledge transfer from older to younger employees plays a key role in lessening knowledge loss and maintaining firms’ competitiveness. While the disharmony derived from a salient age difference between younger and older workers hinders such knowledge transfer. This study aims to construct a rapport model to address it. The proposed model was tested using hierarchical multiple regressions with data from 318 respondents. Results show that almost all rapport dimensions facilitate such knowledge transfer; The moderating role of supportive climate is strong that it enhances or replaces the effects of rapport dimensions on such knowledge transfer. These findings help firms leverage rapport and supportive climate to enhance this invaluable knowledge transfer.